2000
DOI: 10.1046/j.1365-2362.2000.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coffee on gastric emptying and oro‐caecal transit time

Abstract: Coffee does not affect gastric emptying of a liquid meal or small bowel transit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
2
13
0
2
Order By: Relevance
“…This is agreement with some studies (Boekema, Lo, Samsom, Akkermans, & Smout, 2000;Franke et al, 2008), but not others (Akimoto et al, 2009;Lien, Chen, Chang, Kao, & Wang, 1995). Prior studies reporting unaltered gastric emptying utilised 1675-2500 kJ test meals (Boekema et al, 2000;Franke et al, 2008) while studies reporting accelerated gastric emptying have utilised 400-800 kJ liquid boluses (Akimoto et al, 2009;Lien et al, 1995). Thus, it is probable that the energy content and form of the meal influences the impact of coffee on gastric emptying, with low-energy, liquid boluses emptying faster than higher-energy, solid meals.…”
Section: Gastric Emptyingsupporting
confidence: 94%
See 1 more Smart Citation
“…This is agreement with some studies (Boekema, Lo, Samsom, Akkermans, & Smout, 2000;Franke et al, 2008), but not others (Akimoto et al, 2009;Lien, Chen, Chang, Kao, & Wang, 1995). Prior studies reporting unaltered gastric emptying utilised 1675-2500 kJ test meals (Boekema et al, 2000;Franke et al, 2008) while studies reporting accelerated gastric emptying have utilised 400-800 kJ liquid boluses (Akimoto et al, 2009;Lien et al, 1995). Thus, it is probable that the energy content and form of the meal influences the impact of coffee on gastric emptying, with low-energy, liquid boluses emptying faster than higher-energy, solid meals.…”
Section: Gastric Emptyingsupporting
confidence: 94%
“…This study found no significant differences in gastric emptying parameters when coffee or caffeine was co-ingested with a meal. This is agreement with some studies (Boekema, Lo, Samsom, Akkermans, & Smout, 2000;Franke et al, 2008), but not others (Akimoto et al, 2009;Lien, Chen, Chang, Kao, & Wang, 1995). Prior studies reporting unaltered gastric emptying utilised 1675-2500 kJ test meals (Boekema et al, 2000;Franke et al, 2008) while studies reporting accelerated gastric emptying have utilised 400-800 kJ liquid boluses (Akimoto et al, 2009;Lien et al, 1995).…”
Section: Gastric Emptyingsupporting
confidence: 81%
“…It increases the absorption rate of drugs by fastening the gastric emptying rate and makes the drug available for absorption faster [ 8 , 30 ]. Nevertheless, coffee does not have any significant effect on the gastric emptying of liquid medications [ 31 ].…”
Section: Effect Of Coffee On Pharmacokinetics Of Drugsmentioning
confidence: 99%
“…Gastric emptying time can also affect a postprandial blood pressure drop in patients with type 2 diabetes mellitus [12]. However, it is controversial whether caffeine can affect gastric emptying in patients with postprandial hypotension; while some studies reported that caffeine accelerated gastric emptying [13,14], others showed no differences between caffeine groups and a control group with regard to gastric emptying [15]. In this case, although we did not evaluate changes in gastric emptying time with or without caffeine, the difference of glucose concentration in the initial 30 min of the carbohydrate-rich meal with or without caffeine may reflect that of GIP secretion and accelerated gastric emptying time.…”
Section: Discussionmentioning
confidence: 99%